Chronic Appendicitis: A rare Cause of Recurrent Abdominal pain – A case Report - Neupane, Sunischit Chandra; Tamang, Sujan; Basukala, Sunil; Shrivatav, Abhishek (Medical Journal of Shree Birendra Hospital, 2025)
Chronic appendicitis is a rare, often overlooked cause of recurrent right lower quadrant pain, presenting with vague and intermittent symptoms. Its diagnosis is challenging due to the lack of clear clinical criteria. While imaging tools like ultrasound and CT scan aid evaluation, definitive diagnosis requires histopathology. Despite its low incidence, chronic appendicitis should be considered in patients with unexplained, persistent abdominal pain. Early recognition and timely surgical management can provide complete symptom relief and prevent delays in treatment. Including it in the differential diagnosis is essential to avoid missed or delayed intervention.